Lessons from the humanitarian disaster logistics management: A case study of the earthquake in Haiti. Issue 4 (21st March 2020) - Salam, Mohammad Asif; Khan, Sami A.
Abstract : Purpose: The purpose of this study is to draw lessons for logistics management in humanitarian disasters, using the earthquake in Haiti as a case study. In Haiti, there were problems with the logistical response. This study investigates the humanitarian logistics challenges faced by various stakeholders in Haiti during the disaster-relief operations. Design/methodology/approach: In this exploratory case study, the central methodology used was data triangulation. Data triangulation involved interviews with respondents grouped into three categories, non-governmental organizations (NGOs), the military establishment and the governmental agencies. Prominence is given to the common themes expressed by each group. These common themes are then compared to the themes of other groups to identify opportunities and problems for future disaster relief operations. Findings: The study indicates that there is a clear gap in terms of how the humanitarian efforts were coordinated between different actors. Lack of civil–military cooperation and coordination was one of the findings from the interviews, and many of the resources and initiatives were overlapping or redundant. Timeliness and efficiency need to be at the forefront of all planning and would result in more saved lives and reduced human suffering. The key goal of humanitarian logistics stipulates is to form connections and relationships, which was well illustrated through the informants' interviews. It was found that organizing different stakeholders/actors to work together by sharing processes and distribution channels demands a vision that goes beyond logistics management. Government agencies, the military establishment, NGOs, locals and victims need to collaborate to create a synergy in generating solutions that are tailored to the shock of the disaster in the first place. Research limitations/implications: The current study relies on a single case study approach as disaster scenarios are unique in terms of their impact, magnitude, timing and location. Despite these limitations, this study provides a detailed account of the logistical challenges in dealing with the disaster that took place in Haiti. The logistics-related lessons learned from this case study should be carefully applied in other settings, taken into consideration contextual differences. Practical implications: One important aspect of measuring efficiency for any commercial logistics system is key performance indicators (KPIs) that indicate how well the firm is doing in managing its inbound and outbound operations. From a practical standpoint, the Haiti case raised a challenging concern with regard to how to measure the performance of humanitarian disaster logistics. This is a starting point to understand the dynamics of disaster system efficiency and logistics interplay and offers a few lessons to improve the resource availability in the case of future emergencies. Originality/value: This study lays the groundwork for future researchers to explore and debrief on the topic once disaster relief draws to a close and time has allowed logisticians and relief workers to analyze the response mechanisms used in disasters.